Incorporating AI Tool Along with Traditional Method for Speaking Assessment - Umaroh, Liya; Mukaromah, Mukaromah; Naufal, Muhammad; Harisa, Ardiawan Bagus (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2023)
This work focused on incorporating AI tool with traditional method for speaking assessment. The descriptive qualitative has been implemented to complete this research. Problem encountered during English pronunciation was failing to distinguish between short vowel and long vowel. By employing traditional and AI tool, students got numerous benefits. They may enjoy learning with the flexibility of time and they also can engage face to face interaction while using traditional method furthermore, it is essential to acknowledge AI tool with the limitation and drawbacks. AI tool do not give the same stage of personal interconnection and on-going response as a human facilitator.